Phenotypic characterization and microsatellite markers based genetic evaluation of Kalahandi goats - MISHRA, PRIYANKA; ALI, AYESHA S; AGGARWAL, R A K; DIXIT, S P; DASH, S K; DANGI, P S; TYAGI, NEHA; VERMA, N K (The Indian Journal of Animal Sciences, 2015)
Sporadic information is available on morphological traits of Kalahandi, a medium size non-descript goat population of Kalahandi district of Odisha, but no information is found on its genetic diversity. Therefore, an attempt was made to measure the genetic diversity in Kalahandi goat population using 25 microsatellite markers. Genomic DNA isolated from blood samples drawn at random from 50 individuals were utilized for this study. PCR amplified products were used for genotyping on the automatic DNA sequencer. The data were analysed applying different softwares to estimate the various measures of genetic diversity. The average number of observed allele was 11.08 and the effective average number of allele was 4.29. The observed heterozygosity ranged from 0.11 to 0.98 and the expected heterozygosity from 0.11 to 0.87 respectively. Average PIC value ranged from 0.45 (ILSTS044) to 0.91 (OMHC1) with the average value 0.79. Average Fis value for markers tested in Kalahandi goat population ranged from 0.07 at ILSTS030 to 0.67 at OarAE129. Among the negative values it ranged from -0.36 (RM088) to -0.02 (ILSTS029). The mean F value was 0.02. There was no genetic bottleneck observed in Kalahandi goat population. The results suggested that all the microsatellite markers were highly polymorphic and suitable for molecular characterization of Kalahandi goats. There was substantial genetic variation and polymorphism across the studied loci in Kalahandi goats and the population was not in H.W equilibrium but in mutation drift equilibrium. The low inbreeding observed in Kalahandi flocks is a favourable parameter to formulate the appropriate breeding strategies to enhance heterozygosity in the population.